ANALISIS PENGARUH PEMBERIAN INSENTIF TERHADAP PENYELESAIAN KREDIT MACET DI PERUSAHAAN ADIRA PONTIANAK - B01107099, Agung Satriandi (Jurnal Pembangunan dan Pemerataan, 2014)
This study, entitled " Effect of incentives on the settlement of bad loans in the company Adira Pontianak " . The purpose of this study was to determine the effect of a significant incentive to the settlement of bad loans in the company Adira Pontianak . This is an opportunity for the authors to apply the knowledge gained in college and then applied under field conditions with all its problems , especially regarding the provision of incentives to assist company management in an effort to increase the loan resolution . Â  In this study the authors used survey method using the population are employees of the collection of bad debts in the PT . Adira Pontianak . Samples were taken in proportion to the number of samples of 68 respondents . Â  From the research it can be concluded that the magnitude of the contribution or the effect of incentives on loan resolution can be seen from the results of coefficient ( R ) obtained is 0.335 . The contribution of independent variables on the dependent variable in the show through the coefficient of determination (R2) (Adjusted R Square) of 0.112 (0.112 x 100%) = 11.2 % . With the results of significance test sig . = 0.005 which is smaller alpha value of 0.05 ( 0.005 < 0.05 ) so that it can be concluded that there is significant influence of the aspect of giving incentives to loan resolution .